Theoretical study of transport properties of nanoelectronics for sensor application - Ijeomah, Geoffrey Ugochukwu (2018)
Experimental prediction of transport properties of semiconductor devices faces a challenge these days due to continuous device scaling. As nanoelectronics are scaled to nanometre scale lengths, the collision-dominated transport equations used in current device simulators can no longer be applied. On the other hand, the use of a better, more accurate non-equilibrium Green function (NEGF) is hampered by the fact that it requires prohibitive amounts of memory and computation time. This work employs the Boltzmann Transport Equation (BTE) to investigate the transport properties of nanoelectronics, aiming to understand their sensing mechanism. Previous works on solving the BTE have employed either an approximate method or a stochastic method, both of which do not possess the requisite properties for practical device applications. Therefore, this work describes the direct theoretical solution of BTE for nanoelectronics that can be utilized for practical applications. This is achieved by employing powerful theoretical models to discretise the BTE both in energy and momentum without making any approximations on the transport integral or distribution function. This approach is not only fast but also has low memory requirements because it does not require direct storage of matrix elements. The complete spectrum of transport in nanoelectronics extending from Ohmic to high electric field through ballistic transmission is examined to delineate plethora of participating mean free paths (mfps). The transport for arbitrary values of electric field is based on BTE applied to experimental data on nanoelectronics extending from low to high field. In the limit of low field, the mobility expressions are obtained in terms of mfp that is distinctly shorter than the length of the sample. The results indicate that nanoelectronics predominantly operate in quasi-ballistic regime, where carrier transport becomes near ballistic across the channel near the source. The ohmic resistance was found to be quantized with a value of 6.453kΩ consistent with experimental observations with ballistic transmission almost unity as channel length shrinks below the scattering-limited mfp. The emission of a quantum was found to lower the saturation velocity that is independent of scattering and hence ballistic. Transition to ballistic regime was found to occur when channel length is reduced below the ballistic mfp that is shown to be extended version of long-channel mfp modified by injection from the contacts, yet the mobility degrades. This mobility degradation is shown to be the cause of resistance quantum in the low-channel-length limit. These findings have overwhelming implications in nanoelectronics sensor application.